2005
DOI: 10.1101/gad.1304105
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Bak is sequestered by Mcl-1 and Bcl-xL, but not Bcl-2, until displaced by BH3-only proteins

Abstract: Commitment of cells to apoptosis is governed largely by the interaction between members of theSupplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

89
1,248
5
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,144 publications
(1,359 citation statements)
references
References 61 publications
89
1,248
5
2
Order By: Relevance
“…Currently, it has been suggested that Bax translocation could be initiated by either BH3-only Bcl-2 family proteins or by the sequestration of anti-apoptotic proteins (Eskes et al, 2000;Kuwana et al, 2005;Willis et al, 2005). Pagliari et al (2005) have shown that heat treatment alone could lead to a direct activation of Bax.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it has been suggested that Bax translocation could be initiated by either BH3-only Bcl-2 family proteins or by the sequestration of anti-apoptotic proteins (Eskes et al, 2000;Kuwana et al, 2005;Willis et al, 2005). Pagliari et al (2005) have shown that heat treatment alone could lead to a direct activation of Bax.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recent data indicate that antiapoptotic Bcl-2 family members distinctly control the proapoptotic activity of Bax or Bak (Chen et al, 2005b;Gelinas and White, 2005). Proapoptotic Bak is controlled preferentially by Bcl-x L and Mcl-1 until released by proapoptotic signals, that is, by Noxa (Mcl-1) and Bad (Bcl-x L ) (Willis et al, 2005). These proteins appear to play selective roles, which may delineate a higher degree of specificity to the regulation of Bax and Bak in p14 ARF -induced cell death in analogy to other apoptosis-promoting stimuli (Theodorakis et al, 2002;Gillissen et al, 2003;Yu et al, 2003;von Haefen et al, 2004;Wendt et al, 2005), which clearly demands further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the proapoptotic activity of Bax and Bak is hold in check by distinct antiapoptotic Bcl-2 family members. Finally, BH3-only proteins have recently been shown to preferentially activate either Bax-or Bak-dependent events in human cells Gillissen et al, 2003;Yu et al, 2003;Willis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…21 BAX and BAK bind to and are inhibited by different BCL-2-like pro-survival proteins to different extents. 22,23 BOK shares significant homology across all four BH domains to BAX and BAK; however, its role in apoptosis remains unclear, 24 although it may cooperate with BAX in the attrition of primordial follicle oocytes during ageing. 25 The pro-apoptotic BH3-only proteins (BIM, PUMA, BID, BAD, BIK, BMF, NOXA, HRK) share only the BH3 domain with each other and their more distant relatives.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%